Estudo da formação de depósitos inorgânicos em campos petrolíferos - Almeida Neto, José Bezerra de (2012)
Much of the world's oil and gas comes from continental platforms today, including the Atlantic marginal basins along the Brazilian coast. Campos Basin is the use of intense injection of seawater for secondary recovery and, as a consequence, there will be a significant increase in the amount of water produced in the coming decades. The injection and formation water are frequently incompatible under the chemical point of view, and hence its mixture may result in the appearance of salt precipitation in the reservoir, in the wellbore-formation interface, surface and subsurface equipments. The salt scales are undesirable sub products of secondary recovery by water injection. Traditionally, the water produced in offshore fields, after a treatment is discharged into the sea or possibly reinjected to maintain reservoir pressure. The aim of this dissertation was, from production/injection pattern, to study the formation of inorganic deposits in oil fields through evaluation of potential losses observed in producing wells, supporting information to aid in the optimization of schedules for future interventions recovery of well productivity. The study was conducted using a numerical simulator called InorscaleTM, with limitations such as: temperature (20 º to 125 º C), pH (5.5 to 8.5) and lower salinity than 200,000 ppm, based on chemicals and thermodynamic concepts from production history from five analyzed wells. The impact of inorganic scale in the productivity of these wells was demonstrated by the behavior of the productivity index (PI) according to the precipitated mass (PM) of the inorganic salts evaluated, as well as the saturation index (SI) as a function of seawater produced (SW). This study demonstrated that, for the same concentration of precipitated inorganic salt, the barite (BaSO4) represented a major damage to production, compared to other evaluated salts. This knowledge becomes imperative with regard to increasing costs and the complexity of the workover operations (recompletion and stimulation) in the producing wells. In this scenario, preventive action, in order to reduce costs of production, gains importance.